Experimental analysis of advanced control technique for a five‐phase direct matrix converter based on space vector PWM - Rahman, Khaliqur; Sarwar, Adil; Tariq, Mohd; Urooj, Shabana; Bakhsh, Farhad Ilahi; Iqbal, Atif; Ahmad, Salman; Islam, Md. Rasidul (IET power electronics, 2023)
The multiphase matrix converter outperforms the conventional three‐phase system with higher fault tolerance capability and higher power control competency. This paper discusses the direct control based on different possible switching combinations of a three‐phase to five‐phase matrix converter (MC). The proposed control topology significantly reduces the switching commutations in a switching cycle when compared with its counterpart. The control is based on the modified space vector pulse width modulation (SVPWM) strategy. The proposed space vector scheme intelligently selects the voltage vectors to get the desired output characteristics with the least possible switching transitions in a switching cycle. Three possible cases exist in controlling space vectors based on their magnitude, the number of active switching vectors, and their commutations. The results for three different cases of SVPWM have been presented and compared. The total harmonic distortion (THD) obtained in the output is lower in case 2; however, it suffers from a higher common‐mode voltage (CMV). The scheme has been successfully implemented and verified in hardware.